Shooting up : counterinsurgency and the war on drugs - Felbab-Brown, Vanda (Brookings Institution Press, 2010)
Shooting Up analyzes how involvement in the production and trafficking of illicit commodities, especially drugs, affects the strength of belligerents and governments. Much of U.S. anti-narcotics policy abroad is based on the assumption of symbiotic relationships between drug producers, traffickers, insurgents, and terrorists; thus, policy is organized around the premise that the suppression of drug production will service both anti-drug and counterterrorist goals. The author challenges this "narcoguerrilla" premise of U.S. policy. She shows that, far from being complementary, anti-narcotics an